Study on Optimization of Process Parameters and Microstructure Properties of Laser-Cladded AlCoCrFeNi2.1 Eutectic High Entropy Alloy - LI Zansong, WANG Dongsheng (Cailiao Baohu, 2025)
In order to investigate the effects of processing parameters on the microstructure and mechanical properties of the AlCoCrFeNi2.1 eutectic high entropy alloy(EHEA)， an orthogonal experimental design coupled with a comprehensive-scoring method was used to preliminarily identified the optimal laser cladding conditions.Among the tested combinations， Sample 4 (laser power 1 800 W， scanning speed 360 mm/min， powder-feed rate 2.1 r/min) and Sample 5 (laser power 1 800 W， scanning speed 420 mm/min， powder-feed rate 2.4 r/min)received the highest scores.These two specimens were then subjected to multi-pass， single-layer laser cladding， and their microstructures and mechanical properties were systematically characterized.Results showed that the laser-cladded AlCoCrFeNi2.1 EHEA coating was composed predominantly of dual FCC and BCC phases.In the multi-pass coating， Sample 5 displayed a surface dominated by uniform equiaxed grains，whereas Sample 4 exhibited a mixture of columnar and equiaxed grains with larger， irregular sizes.Further investigations showed that Sample 5 possessed superior microhardness and wear resistance:an average hardness of 323.7 HV1.0，an average friction coefficient of 0.64，and markedly lower wear rate (1.16×10－6 mm3∙N－1∙mm－1) and wear volume (14.4 mm3) than Sample 4.Accordingly， the optimal laser-cladding parameters for AlCoCrFeNi2.1 EHEA were determined to be a laser power of 1 800 W， a scanning speed of 420 mm/min， and a powder-feed rate of 2.4 r/min.